Effectiveness of Positron Emission Tomography for Predicting Chemotherapy Response in Colorectal Cancer Liver Metastases - Glazer, Evan (2010)
Hypothesis Chemotherapeutic agents may be able to convert unresectable colorectal hepatic metastasis to resectable disease, therefore changing the surgical options. The role of positron emission tomography (PET) for patients undergoing chemotherapy remains unclear. We hypothesize that recent chemotherapy treatment could result in false-negative PET results. Design Case-control study evaluating PET findings. Setting The University of Texas M. D. Anderson Cancer Center. Patients From May 1, 2006, through August 31, 2008, data for 224 consecutive patients were entered into a prospective database for evaluation of hepatic metastasis of colorectal carcinoma. One hundred thirty-eight patients underwent PET and conventional imaging (a combination of computed tomography, magnetic resonance imaging, and ultrasonography). All had oncologically sound colorectal operations. Interventions Liver resection or ablation for colorectal liver metastases. Main Outcome Measures To determine the accuracy of PET scans to detect residual viable colorectal cancer liver metastases after a significant response to systemic chemotherapy. Results Patients with biopsy-proven disease underwent hepatic resection (120 patients [87.0%]), radiofrequency ablation (2 [1.4%]), or resection with radiofrequency ablation (7 [5.1%]). Nine patients (6.5%) had inoperable disease that was found intraoperatively. When performed within 4 weeks of chemotherapy, PET had a negative predictive value of 13.3% and a positive predictive value of 94.3%. The sensitivity was 89.9%, the specificity was 22.2%, and the accuracy was 85.5%. Conclusions Positron emission tomography within 4 weeks of chemotherapy is not a useful test for evaluation of colorectal hepatic metastases. The high rate of false-negative results is likely due to metabolic inhibition caused by chemotherapeutic drugs. We recommend that physicians not use PET in patients recently completing chemotherapy; they should undergo the appropriate oncologic hepatic operation based on the high probability of viable malignant disease. The role of surgery in colorectal hepatic metastases is undergoing a revolution of sorts. For example, a few years ago an extrahepatic metastasis effectively eliminated surgical resection, but a combination of chemotherapeutic options and surgical techniques has expanded the indications for resection and increased the population of patients who may benefit.1,2 Neoadjuvant chemotherapy has increased the resectability rate by 11% to 37%.1 Unfortunately, greater than 80% of patients undergoing hepatic resection will have recurrences, mostly within the first 2 years.2 Nonetheless, the only hope for cure is resection, and prior surgical dogma based on the number of lesions, size of the tumor-free resection margin, and presence of resectable extrahepatic disease must be questioned.3- 5 The current standard approach to surgical planning is contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) for specific tumor characteristics or contraindications to CT.6 Several series showed that focal extrahepatic disease, an isolated pulmonary lesion, can be safely resected, with 5-year survival rates of 29% to 58%.7,8 In 1 series,7 17 of 30 patients required 3 or more resections. Clearly, this is an extremely selected patient population. As the opportunities to resect hepatic and focal extrahepatic colorectal metastases continue to improve, choosing the appropriate patient population becomes imperative. Imaging modalities such as CT and MRI provide detailed anatomic information regarding the nature of the lesion but no functional information. Transcutaneous ultrasonography is even less invasive but often less accurate.9 Finally, positron emission tomography (PET) using fluorine-18–labeled deoxyglucose detects increased metabolic activity (uptake). This can represent metastatic disease, new primary disease, infectious causes, inflammation, or any increase in the cellular use of glucose. At present, the poor anatomic resolution of PET does not allow for its isolated use to plan operations; however, it is often used in combination with CT and/or MRI for diagnostic imaging.1,6,9 Exactly what PET adds to surgical decision making remains unclear. A meta-analysis9 found that PET had higher sensitivity rates (76%) for detection of malignant lesions than did helical CT (64%) or MRI (71%). That meta-analysis included 61 articles from 1990 to 2003. The criterion standard applied was pathologic tissue diagnosis. Chemotherapy changes the activity of a malignant lesion,1,10,11 but exactly how much is unclear. There appears to be a correlation between decreasing PET uptake and reduction in tumor burden; however, hypometabolic lesions may still harbor viable malignant cells.10,11 In addition, the authors reviewed the temporal relationship between chemotherapy and false-negative and false-positive results on PET. The false response rate has been reported to be up to 20% if PET is performed within 5 weeks of chemotherapy treatment.10 Thus far, similar studies11 have had too few patients to reach a conclusive decision regarding the role of PET in colorectal hepatic metastases. Therefore, we reviewed our patient population for the temporal relationship between PET results and tissue-proven hepatic metastases from colorectal carcinoma. The impetus for this research was finding viable cancer in patients with clearly negative findings on PET. We hypothesized that PET uptake levels were artificially decreased after chemotherapy. That is, lesions that appeared to be nonmalignant were actually viable malignant lesions.